Correlation between Insulin-Like Growth Factor I and Skeletal Maturity Indicators. (April 2021) - Carelli, Julia; Mattos, Camila; Morais, Nathaly D.; Scariot, Rafaela; Brancher, João Armando; Baratto-Filho, Flares; Kuchler, Erika Calvano; Moro, Alexandre
Objective: The purpose of this study was to evaluate the correlation between the growth maturity indicators in orthodontic patients. Design : This cross-sectional study was performed on 37 orthodontic patients (17 males and 20 females). An anamnesis, clinical and image examination, and blood sample collection were performed. The inclusion criteria were non-syndromic Class II patients of both gender, age ranging between 10 to 16 years. The lateral cephalometric radiographs were evaluated using 6-stage cervical vertebrae maturation (CVM) technique. The hand-wrist radiographs were staged using the 11-stage skeletal maturation indicator (SMI) technique. Blood was collected in the same week of the images to quantify IGF-1 levels in serum. Data were tested for normality by Shapiro–Wilk test. The Pearson test was used to determine the correlation strength between the variables (alpha of 5%). Results : A strong correlation was observed only between SMI stages and CVM stages in the total sample (r=0.864; p<0.0001) and according to the gender (r=0.793; p<0.0001 for females; and r=0.753; p<0.0001 for males). IGF-1 was only moderately correlated with SMI stages and CVM stages. Conclusion : Hand-wrist and cervical vertebral stages were strongly correlated among them, however, IGF-1 was only moderately correlated with both skeletal maturity indicators.